The Socio-Economic Impact of Universal Postal Services in Indonesia: A Strategic Analysis of PT Pos Indonesia’s Public Service Obligation - Prastyantoro, Riharsono; Purnomo, Agus; Saputra, Arfyan (Dinasti International Journal of Management Science, 2025)
This study analyzes the socio-economic impact of the Universal Postal Service (Layanan Pos Universal/LPU) operated by PT Pos Indonesia (Persero) under the Public Service Obligation (PSO) scheme. A quantitative framework combining counterfactual analysis, Local Multiplier 3 (LM3), and input–output analysis was developed to assess benefits for the public, government, and MSMEs. In 2024, a government subsidy of IDR 392 billion generated IDR 1.88 trillion in travel cost savings, contributed 0.238% to GDP through social assistance distribution, and supported MSME output with a 17.5% contribution per 1% national growth. The findings highlight LPU’s strategic value for sustainable, benefit-based funding.